Posterior Fossa Tumor in Children - TABATABAEI, Seyed Mahmoud; SEDDIGHI, Afsoun; SEDDIGHI, Amir Saied (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Tabatabaei SM, Seddighi A, Seddighi AS. Posterior Fossa Tumor in Children. Iran. J. Child. Neurol 2012;6(2): 19-24. Objective Primary brain tumors are the most common solid neoplasms of childhood, representing 20% of all pediatric tumors. The best current estimates place the incidence between 2.76 and 4.28/100,000 children per year. Compared with brain tumors in adults, a much higher percentage of pediatric brain tumors arise in the posterior fossa. Infratentorial tumors comprise as many as two thirds of all pediatric brain tumors in some large series. Tumor types that most often occur in the posterior fossa include medulloblastoma, ependymoma, cerebellar astrocytoma and brainstem glioma. Materials & Methods All pediatric cases of posterior fossa tumor that were considered for surgery from 1981 to 2011 were selected and the demographic data including age, gender and tumor characteristics along with the location and pathological diagnosis were recorded. The surgical outcomes were assessed according to pathological diagnosis. Results Our series consisted of 84 patients (52 males, 32 females). Cerebellar symptoms were the most common cause of presentation (80.9%) followed by headache (73.8%) and vomiting (38.1%). The most common histology was medulloblastoma (42.8%) followed by cerebellar astrocytoma (28.6%), ependymoma (14.3%), brainstem glioma (7.2%) and miscellaneous pathologies (e.g., dermoid, andtuberculoma) (7.2%). Conclusion The diagnosis of brain tumors in the general pediatric population remains challenging. Most symptomatic children require several visits to a physician before the correct diagnosis is made. These patients are often misdiagnosed for gastrointestinal disorders. Greater understanding of the clinical presentation of these tumors and judicious use of modern neuroimaging techniques should lead to more efficacious therapies. References 1. Mehta V, Chapman A, McNeely PD, Walling S, Howes WJ. Latency between symptom onset and diagnosis of pediatric brain tumors: an Eastern Canadian geographic study. Neurosurgery 2002 Aug;51(2):365-73. 2. Mueller B, Gurney JG. Epidemiology of pediatric brain tumors. Neurosurg Clin N Am 1992 Oct;3(4):715-21. 3. Albright A, Wisoff JH, Zeltzer PM, Deutsch M, Finlay J, Hammond D. Current neurosurgical treatment of medulloblastomas in children. A report from the Children’s Cancer Study Group. Pediatr Neurosci 1989;15(6):276-82. 4. Albright AL. Posterior fossa tumors. Neurosurg Clin N Am. 1992 Oct;3(4):881-91. 5. Healey E, Barnes PD, Kupsky WJ, Scott RM, Sallan SE, Black PM. The prognostic significance of postoperative residual tumor in ependymoma. Neurosurgery 1991 May;28(5):666-71. 6. Park T, Hoffman HJ, Hendrick EB, Humphreys RP, Becker LE. Medulloblastoma: clinical presentation and management. Experience at the hospital for sick children, Toronto, 1950-1980. J Neurosurg 1983 Apr;58(4):543-52. 7. Allen LC. Childhood brain tumors. Current status of clinical trials in newly diagnosed and recurrent disease. Pediatr Clin North Am 1985 Jun;32(3):633-51. 8. Laurent JP,Cheek WR. Brain tumors in children. J Pediatr Neurosci 1985;1:15-32. 9. O’Brien DF, Caird J, Kennedy M, Roberts GA, Marks JC, Allcutt DA. Posterior fossa tumours in childhood: evaluation of presenting clinical features. Irish Med J 2001 Feb;94(2):52-3. 10. Bronstein KS. Epidemiology and classification of brain tumours. Cri Care Nurs Clin North Am 1995;7:79-89. 11. Lannering B, Marky I, Nordborg C. Brain tumors in children and adolescence in west Sweden 1970-1984. Epidemiology and survival Cancer. l990 Aug 1;66(3):604-9. 12. Cushing H. Experiences with cerebellar astrocytomas: a critical review of 26 cases. Surg Gynae Obstet 1931;52:129-204. 13. Geissinger JD. Astrocytomas of the cerebellum in children. Long-term study. Arch Neurol 1971 Feb;24(2):125-35. 14. Pascual - Castroviejo I, Raimondi AJ, Choux M, Di Rocco C. Functional basis of posterior fossa symptoms and signs. eds. Posterior fossa tumours. New York: Springer Verlag; 1993;12-21. 15. Cohen ME, Duner PK. Tumours of the brain and spinal cord including leukemic infiltrates. In: Swaiman KF, editor. Pediatric neurology principles and practice. St. Louis: Mosby; 1991. p. 94550. 16. Bronstein KS. Epidemiology and classification of brain tumors. Crit Care Nurs Clin North Am 1995 Mar;7(1):79-89. 17. GOL A. Cerebellar astrocytomas in children. Am J Dis Child 1963 Jul;106:21-4. 18. Hojer C, Hildebrandt G, Lanfermann H, Schroder R, Haupt WF. Pilocyticastrocytomas of the posterior fossa. A follow-up study in 33 patients. Acta Neurochir (Wien) 1994;129(3-4):131-9. 19. Lassman LP, Arjona VE. Pontine gliomas of childhood. Lancet 1967 Apr 29;1(7496):913-5. 20. Reigel DH, Scarff TB, Woodford JE. Biopsy of pediatric brain stem tumors. Childs Brain. 1979;5(3):329-40. 21. Griwan MS, Sharma BS, Mahajan RK, Kak VK. Value of precraniotomy shunts in children with posterior fossa tumours. Childs Nerv Syst 1993 Dec;9(8):462-5. 22. Raimondi AJ, Tomita T. Hydrocephalus and infratentorial tumors. Incidence, clinical picture, and treatment. J Neurosurg 1981 Aug;55(2):17482. 23. Jamjoom AB, Jamjoom ZA, al-Rayess M. Intraventricular and leptomeningeal dissemination of a pilocytic cerebellar astrocytoma in a child with a ventriculoperitoneal shunt: case report Br J Neurosurg. 1998 Feb;12(1):568. 24. Vaquero J, Cabezudo JM, de Sola RG, Nombela L. Intratumoral hemorrhage in posterior fossa tumors after ventricular drainage. Report of two cases. J Neurosurg 1981 Mar;54(3):406-8. 25. Hoffman HJ, Hendrick EB, Humphreys RP. Metastasis via ventriculoperitoneal shunt in patients with medulloblastoma. J Neurosurg 1976 May;44(5):562-6. 26. Hirsch J, Renier D, Czernichow P, Benveniste L, PierreKahn A. Medulloblastoma in childhood: survival and functional results. Acta Neurochir 1979;48:1-15. 27. Abdollahzadeh-Hosseini SM, Rezaishiraz H, Allahdini F. Acta Medica Iranica 2006;44(2):89-94.